La nueva planta para la Casa Real de Fernando VII: El desconocido Reglamento de 17 de noviembre de 1815 - Sánchez González, M.ª Dolores del Mar (Cuadernos de Historia Moderna, 2003)
This article discovers the first regulation of the Real House of Fernando VII‚ –The regulation of 17 of November of 1815–, made by the monarch to give a New Plant to organization of same, the agreed one with restoration of absolutism made by the sovereign after its return to Spain in 1814. This it is first of a set of organizations measures that has special importance until to be now not known, by the fact of to have remained written by hand for internal use of its Real House. Evolution of this regulation also appears until his transformations in the one of 1817, the first form and well-known, and the text of the Regulation is included in a documentary Appendices.